Exploration of the medical periodic table: towards new targets - Barry, Nicolas P. E.; Sadler, Peter J. (Chemical communications (Cambridge, England), 2013)
Metallodrugs offer potential for unique mechanisms of drug action based on the choice of the metal, its oxidation state, the types and number of coordinated ligands and the coordination geometry. We discuss recent progress in identifying new target sites and elucidating the mechanisms of action of anti-cancer, anti-bacterial, anti-viral, anti-parasitic, anti-inflammatory, and anti-neurodegenerative agents, as well as in the design of metal-based diagnostic agents. Progress in identifying and defining target sites has been accelerated recently by advances in proteomics, genomics and metal speciation analysis. Examples of metal compounds and chelating agents (enzyme inhibitors) currently in clinical use, clinical trials or preclinical development are highlighted.